P-hacking, data type and data-sharing policy - Abel Brodeur; Nikolai Cook; Carina Neisser (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
In this paper, we examine the relationship between p-hacking and datasharing policies for published articles. We collect 38,876 test statistics from 1,106 articles published in leading economic journals between 2002-2020. While a data-sharing policy increases the provision of research data to the community, we find a well-estimated null effect that requiring authors to share their data at the time of publication does not alter the presence of p-hacking. Similarly, articles that use hard-to-access administrative data or third-party surveys, as compared to those that use easier-to-access (e.g., own-collected) data are not different in their p-hacking extent. Voluntary provision of data by authors on their homepages offers no evidence of reduced p-hacking.
Keywords: A11; B41; C13; C40; I23; 330; p-Hacking; Publication Bias; Data and Code Availability; Data Sharing Policy; Administrative Data; Survey Data